Physical Parameters and Contrasts of Wooden Objects in Lacustrine Environment: Ground Penetrating Radar and Geoelectrics - Annika Fediuk; Dennis Wilken; Tina Wunderlich; Wolfgang Rabbel (Geosciences, 2020)
We investigate how suitable ground penetrating radar (GPR) and geoelectrics are to prospect the remains of submerged wooden archaeological constructions in the water column. For this purpose, we determined the contrasts of electric resistivity and dielectric permittivity from measurements on present-day wood samples, serving as simplified approximations of water saturated and undegraded archaeological wood. As common substitutes of hard and soft construction wood, we investigated oak and spruce wood. The electric resistivity and dielectric permittivity were determined with increasing moisture content from small-scale electric and GPR measurements using a Wenner alpha array and a 2 GHz Palm antenna in a watering experiment. In a water-saturated state, resistivity values of <270 Ωm and relative dielectric permittivity values of >20 were observed. The anisotropy effects and deviations of the wood species were seen to be up to 30%. On the basis of this, the relative material contrasts of wood with respect to fresh water, sand, and clay were calculatedand compared to values found in the literature for seismic contrasts. Geoelectric, GPR, and seismic measurements show contrasts of 0.3 to 0.8, −0.4 to 0.2, and −0.24 to 0.35, depending on the surrounding material and structural orientation of the wood. The highest contrasts were found for wood in fresh water, followed by clayey and sandy subsoils. On the basis of the determined contrasts, analytical calculations were performed showing that an object of 0.5 m diameter can be detected at depths between 0.5 m and 1.5 m with geoelectrics (Schlumberger) and at depths between 0.5 m and 3 m with ground penetrating radar measurements (400 MHz).